Public Relations Implications of the Challenges Facing the Bakassi Internally-Displaced Persons (IDPs) in Nigeria’s Cross River State - Ene Okon, Patrick; Eyo Abu, Patience (International Journal of Emerging Trends in Social Sciences, 2019)
According to the United Nations High Commission for Refugees (UNHCR), “we are now witnessing the highest levels of displacement on record” with an unprecedented 68.5 million people forced from home globally (UNHCR, 2018). Among those affected are the Bakassi people in the Cross River State of Nigeria, who were forced to abandon their ancestral home due to the World Court’s judgment of 10 October 2002 and Greentree Agreement of 12 June 2006 that ceded their oil and natural gas-rich peninsula to Cameroon. This paper aimed at communicating the challenges faced by these people who now live as refugees in their own country as well as assessing the public relations implications of their geographical displacement, social dislocation, and economic dispossession. The study employed the survey method and used the questionnaire to obtain data from 200 internally-displaced persons of Bakassi; as well as unstructured interview to gather additional information from five Government officials and five Bakassi elites who were involved in resettling these people. Egon’s refugee theory (1981), Peter’s social integration theory (1960) and James Grunig’s two-way symmetrical model of public relations (1984) formed the theoretical framework of the study. Data obtained were presented quantitatively, and analysed descriptively. Based on the conclusion that there is a noticeable Public Relations slack in the relationship between Government and the Bakassi IDPs, it was recommended that adequate efforts should be made to fill the observed gaps.